As motivações da participação: uma análise da participação social com base na trajetória da União dos Moradores do Jardim Iracema - UMJIR - Silva, Cícera Maria (2006)
The leading line of this research work is the upshot of a historical confirmation: the growing of political and participative manifestations especially in the 1990 decade having as their origin several social groups within the most varied scenarios. In spite of a dissemination of these outbreaks within the Brazilian society as a whole, one might notice a meaningful participation of poorer strata of the population, especially by community associations within housing projects. The usually given reason for the fact, as a general rule, is the conjuncture of factors such as the consolidation of the globalization process and its developments within cultural, social, political and economic levels especially within the movement for redemocratization of Brazilian society. Undoubtedly those factors should not in any way be overlooked. It is necessary though that a minimal exercise of a relative approach be carried out considering that every subject involved in this process attributes a special meaning to his action. Within this framework, the immediate objective of this study is to unveil the participation drive. In other words, what factors have influenced the “simple men” to social participation? And more: What kind of changes this participation drive has produced in the community and in the social actors involved? The entity that shapes up this study is the União dos Moradores do Jardim Iracema - UMJIR which is situated in the western part of Fortaleza and is being active as an association for twenty two years now leading the struggles of its community.